The Implementation of Zakat Profession By Employees Income in Public Health Center (PHC) Sitopeng Cirebon City - Mohammad Ridwan; Andini Triwulan (Journal of Social Science, 2020)
ZAKAT is an obligation of Muslims as a form of concern fellow a man in establishing the relationship between man and Allah and man's relationship with other humans. With the obligations of zakat, in addition to fostering the relationship with Allah SWT also can tighten the rope the relationship between human beings. The aim of the research is that to identify understanding and application of zakat profession on employee income at Public Health Center Sitopeng Cirebon City. Method used in this research is qualitative method with data collection techniques are observation and interview. Based on the research results obtained it can be concluded that 1. Implementation of professional alms employees on Public Health Center Sitopeng has not been maximized because of the lack of employee understanding of the provisions on professional zakat regarding the law, calculation and distribution of professional zakat. Besides that, there is still a lack of socialization on professional zakat from the government or the nearest Zakat Institution. 2. Employee income at Public Health Center Sitopeng has indeed reached the Regional Minimum Wage (UMR) standard for Cirebon City but for the obligation to fulfill the professional zakat it still does not meet the nishob requirements set by the Islamic Sharia, but employees The Sitopeng Health Center can give a portion of its assets through Shodaqoh or infaq.